Polemik Penafsiran Ziyadah dalam Surah Yunus [10]: 26: Analisis Komparatif Penafsiran di Era Klasik Hingga Pertengahan - khobirul amru (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2021)
This article is motivated by the existence of many versions with regard to the exegeses of term ziya>dah in Surah Yu>nus [10]: 26. To read at a glance concerning those diverse versions frequently feels vague and obscure. Moreover, figures behind all of those versions are exegetes whose integrities and capabilities in Quranic Exegesis are unquestionable, such as Ibn Abi> H{a>tim, al-Ma>turi>diy, al-Ma>wardiy, and Ibn al-Jauziy. This thing becomes the point of departure of the urgency to profoundly scrutinize those diverse versions of the exegeses. There is one question aimed in this article, that is, how quranic exegeses from classical exegetes to medieval exegetes on the term ziya>dah are. Using the comparative analysis, this research results in two significant conclusions. The first is that the exegeses of the term ziya>dah continually evolve periodically. The second is that there is an underlying correlation that is linked between the classical period and the medieval period, that the genealogy of the various exegeses of the term ziya>dah in the medieval period can be found in the classical period.